2011
DOI: 10.1242/jeb.057729
|View full text |Cite
|
Sign up to set email alerts
|

Not all songbirds calibrate their magnetic compass from twilight cues: a telemetry study

Abstract: SUMMARY Migratory birds are able to use the sun and associated polarised light patterns, stellar cues and the geomagnetic field for orientation. No general agreement has been reached regarding the hierarchy of orientation cues. Recent data from naturally migrating North American Catharus thrushes suggests that they calibrate geomagnetic information daily from twilight cues. Similar results have been shown in caged birds in a few studies but not confirmed in others. We report that free-flying Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…Our study is in agreement with a number of recent studies that did not find an effect of cue conflict exposures on the orientation of the corresponding study species (Wiltschko et al, 2008a;Wiltschko et al, 2008b;Gaggini et al, 2010;Chernetsov et al, 2011; but see Muheim et al, 2008). Similar to our study, the authors reported no compass calibration, but instead a simple domination of magnetic or stellar cues over the sunset cues (Chernetsov et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study is in agreement with a number of recent studies that did not find an effect of cue conflict exposures on the orientation of the corresponding study species (Wiltschko et al, 2008a;Wiltschko et al, 2008b;Gaggini et al, 2010;Chernetsov et al, 2011; but see Muheim et al, 2008). Similar to our study, the authors reported no compass calibration, but instead a simple domination of magnetic or stellar cues over the sunset cues (Chernetsov et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The birds were released from the cages when the elevation of the sun was lower than 13.7deg below the horizon, i.e. after nautical twilight, so that stars, when not cloudy, were visible and the skylight polarization pattern had disappeared (see Cochran et al, 2004;Chernetsov et al, 2011). The birds were then held in the open hand, so that they could decide by themselves when and into which direction to depart.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations